I hear the sirens in the street : a Detective Sean Duffy novel - McKinty, Adrian (McKinty, Adrian. Troubles trilogy., 2013)
Detective Sean Duffy investigates the death of an American military veteran in 1982 Ireland and quickly finds himself combatting his romantic instincts, professional misconduct, and powerful men.